Pediatric asthma control in Asia: Phase 2 of the Asthma Insights and Reality in Asia‐Pacific (AIRIAP 2) survey. Issue 4 (18th February 2013) - Wong, G. W. K.; Kwon, N.; Hong, J. G.; Hsu, J.‐Y.; Gunasekera, K. D.
Abstract Background We conducted Phase 2 of the Asthma Insights and Reality in the Asia‐Pacific (AIRIAP 2) survey in 2006 to determine the level of asthma control in this region and the validity of the Asthma Control Test™ (ACT) and childhood ACT (C‐ACT) in relation to asthma control. Methods Pediatric participants (0 to <16 years; N = 988) with diagnosed asthma and current asthma symptoms or taking anti‐asthma medications were recruited from 12 geographic areas in Asia. The survey consisted of the AIRIAP 2 questionnaire (asthma symptoms, use of urgent healthcare services and anti‐asthma medication) and the ACT or C‐ACT (English or Chinese translations only), both administered in the participant's preferred language. A symptom control index based on the Global Initiative for Asthma criteria (except lung function) was used to classify asthma control status. Results Most participants had inadequately controlled asthma ('uncontrolled' = 53.4%, 528/988; 'partly controlled' = 44.0%, 435/988). Only 2.5% (25/988) had 'controlled' asthma. Demand for urgent healthcare services (51.7%, 511/988) and use of short‐acting beta‐agonists (55.2%, 545/988) was high. The optimal ACT and C‐ACT cutoff score for detecting uncontrolled asthma (compared with controlled or partly controlled asthma) was determined to be ≤19 (receiver operating characteristic analysis) with good agreement between the ACT and C‐ACT and the symptom control index. Conclusions Findings from this survey show that asthma control is suboptimal in many children in the Asia‐Pacific region. Practical tools, such as the ACT or C‐ACT, may help clinicians assess asthma control and facilitate adjustment of asthma medication.